Spatial Assessment of Ecosystem Services from Planted Forests in Central Vietnam - Paudyal, K.; Samsudin, Y.B.; Baral, H.; Okarda, B.; Vu, T.P.; Paudel, S.; Keenan, R.J. (MDPI, 2020)
Globally, planted forests are increasing, providing increased resources to forest industries and ecosystem services (ES) to local and wider communities. However, assessment of the impacts of plantations on ES has been limited. Planted forests have expanded rapidly in Vietnam over the last 20 years, with much of the planting undertaken by smallholder growers using exotic Acacia and Eucalyptus species. This study aimed to test a framework to assess changes in four ES due to an increase in Acacia plantations from 2005–2015 in central Vietnam: carbon sequestration, sediment retention, water yield and habitat. Quantitative and qualitative indicators for each service were derived from the literature. Results showed that the area of planted forests in Quảng Trị and Thừa Thiên-Huế Provinces increased from 130,930 hectares (ha) to 182,508 ha, mostly replacing non-forest areas (degraded lands, grasslands and agricultural lands) and poor forests. The framework demonstrated capacity to assess the effect of planted forests on wood flow, carbon stocks, sediment retention, streamflow and the extent of wildlife habitat. Apart from the wood supply and carbon sequestration, more research is required to translate biophysical indicators to benefit relevant indicators related to human welfare. The study also revealed that the area of rich forests decreased by 20% over the ten years, mostly through degradation to poorer quality natural forests. Therefore, at the landscape scale, improvement in ES due to conversion of non-forests to planted forests was offset by a reduction in some services as a result of degradation of native forest from rich to poorer condition. Assessment of changes in ES due to planted forests also needs to consider other landscape changes. These analyses can inform policymakers, forest owners and managers, environmental organizations and local communities of the benefits and impacts of planted forests and provide an improved basis for payments for ES and potential additional income for smallholder tree growers.